New solitary wave solutions to the (2+1)-dimensional Calogero-Bogoyavlenskii-Schiff and the Kadomtsev-Petviashvili hierarchy equations - Baskonus, H. M.; Sulaiman, T. A.; Bulut, H. (Indian Assoc Cultivation Science, 2017)
In this paper, with the help of Wolfram Mathematica 9 we employ the powerful sine-Gordon expansion method in investigating the solution structures of the two well known nonlinear evolution equations, namely; Calogero-Bogoyavlenskii-Schiff and Kadomtsev-Petviashvili hierarchy equations. We obtain new solutions with complex, hyperbolic and trigonometric function structures. All the obtained solutions in this paper verified their corresponding equations. We also plot the three- and two-dimensional graphics of all the obtained solutions in this paper by using the same program in Wolfram Mathematica 9. We finally submit a comprehensive conclusion.
Keywords: Sine-Gordon expansion method; Calogero-Bogoyavlenskii-Schiff equation; Kadomtsev-Petviashvili hierarchy equation; Complex function solutions; Hyperbolic function solutions; Trigonometric function solutions